2009
DOI: 10.1073/pnas.0907063106
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory perceptual learning requires adult neurogenesis

Abstract: Perceptual learning is required for olfactory function to adapt appropriately to changing odor environments. We here show that newborn neurons in the olfactory bulb are not only involved in, but necessary for, olfactory perceptual learning. First, the discrimination of perceptually similar odorants improves in mice after repeated exposure to the odorants. Second, this improved discrimination is accompanied by an elevated survival rate of newborn inhibitory neurons, preferentially involved in processing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
268
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(284 citation statements)
references
References 28 publications
13
268
1
2
Order By: Relevance
“…Sensory experience might promote cell survival during a specific critical window, when new neurons receive synaptic inputs from preexisting circuits (6-9) and exhibit long-term potentiation (LTP) (10). During this window, an odor-reward association task (but not a mere odor exposure) promotes cell survival (11,12) and specific activation of adult-born neurons monitored through immediate early gene labeling (13,14). As a result, olfactory memory is impaired when adult neurogenesis is compromised (13,15).…”
mentioning
confidence: 99%
“…Sensory experience might promote cell survival during a specific critical window, when new neurons receive synaptic inputs from preexisting circuits (6-9) and exhibit long-term potentiation (LTP) (10). During this window, an odor-reward association task (but not a mere odor exposure) promotes cell survival (11,12) and specific activation of adult-born neurons monitored through immediate early gene labeling (13,14). As a result, olfactory memory is impaired when adult neurogenesis is compromised (13,15).…”
mentioning
confidence: 99%
“…The work of Breton-Provencher et al, together with recently published analyses of animals with impaired adult neurogenesis provides us with precious food for thought concerning the possible role of new neurons (Imayoshi et al, 2008;Clelland et al, 2009;Deng et al, 2009;Kitamura et al, 2009;Lazarini et al, 2009;Moreno et al, 2009;Valley et al, 2009). The contrasting results obtained in different studies blocking adult neurogenesis and assessing olfactory behavior highlight the need for further investigations to decipher the precise function of adult neurogenesis for the sense of smell.…”
Section: Frontiers In Neuroscience | Neurogenesismentioning
confidence: 98%
“…Overall, these independent studies seem to show, consistently, that blocking adult neurogenesis in the OB does not affect spontaneous discrimination between different odors (Imayoshi et al, 2008;Breton-Provencher et al, 2009;Lazarini et al, 2009). However, another recent study showed that blocking adult neurogenesis resulted in a dramatic decrease in performance in a task involving discrimination between two perceptually similar odorants after passive exposure (Moreno et al, 2009). Unlike BretonProvencher et al, Lazarini et al reported that the blockade of adult neurogenesis had no effect on odor detection thresholds.…”
Section: Influence Of the Blockade Of Adult Neurogenesis On Olfactorymentioning
confidence: 99%
See 2 more Smart Citations